Nephrotoxicity in rabbits after long-term nandrolone decanoate administration. (30th September 2016) - Tsitsimpikou, Christina; Vasilaki, Fotini; Tsarouhas, Konstantinos; Fragkiadaki, Persefoni; Tzardi, Maria; Goutzourelas, Nikolaos; Nepka, Charitini; Kalogeraki, Alexandra; Heretis, Ioannis; Epitropaki, Zoi; Kouretas, Dimitrios; Tsatsakis, Aristidis M.
Highlights: Nephrotoxic effects of nandrolone decanoate on young rabbits. Significant increase in serum urea and creatinine. Hypereamia, fibrosis and focal inflammation in kidney tissue of high-dosed rabbits. Increased telomerase activity in intramuscularly treated animals. Tissue TBARS and GSH levels were significantly altered. Abstract: Among the various side effects of supra-physiological dose of anabolic androgenic steroids that are described, renal toxicity remains the least evaluated. The present study provides evidence that long-term administration of nandrolone decanoate could lead to alterations of renal function and structure in the experimental rabbit model. A pronounced increase in serum urea, creatinine, SGOT and SGPT is observed in the treated animals, with intramuscular administration being more detrimental. Histopathological evaluation of kidneys indicated hyperaemia, fibrosis and focal inflammation. Furthermore, the significantly increased telomerase activity found in the kidneys of the intramuscularly treated animals could possibly represent a counteracting survival mechanism. Oxidative stress markers that were influenced the most were TBARS, indicating lipid peroxidation, and GSH. An interesting finding in our study though, was that while intramuscular administration showed the highest biochemical derangement, oxidative stress markers provided mixed results between intramuscularly and subcutaneously treated rabbits. In conclusion, nephrotoxicity of nandrolone decanoate remains a multi-factorial, partly irreversible effect that involves augmented tissue oxidative status.